Analisis Hubungan Dukungan Suami dengan Perilaku Pencegahan Risiko Tinggi pada Ibu Hamil - Feriani, Pipit; Ernawati, Rini (Jurnal Ners, 2025)
third highest position in ASEAN. High-risk pregnancy can be prevented through optimal preventive behavior, where husband support has a strategic role in increasing pregnant women's compliance with prenatal health protocols. The purpose of this study was to analyze the relationship between husband support and high-risk pregnancy prevention behavior in pregnant women at Lempake Health Center, Samarinda. This quantitative research with cross sectional design involved 268 pregnant women at Lempake Health Center, Samarinda. Sampling used total sampling. Research instruments in the form of validated questionnaires to measure husband support and high-risk prevention behavior. Data analysis used Chi-square test with significance level α=0.05. The proportion of pregnant women with good husband support who were not at high risk was 67.5%, while those at high risk were only 8.6%. In the group with poor husband support, the proportion of non-risk was 14.6% and high risk was 9.3%. Chi-square test results showed p value = 0.000 (p<0.05) with OR = 5.045 (95% CI: 2.89-8.81). There is a significant relationship between husband support and high-risk prevention behavior in pregnant women. Pregnant women with good husband support have 5 times greater chance to implement high-risk prevention behavior compared to those with poor husband support. Keywords: husband support, high-risk pregnancy, prevention behavior, antenatal care